Molecular genetics of herbicide resistance in Palmer amaranth (Amaranthus palmeri): metabolic tembotrione resistance and geographic origin of glyphosate resistance - Küpper, Anita, author; Gaines, Todd A., advisor; Dayan, Franck E., committee member; Nissen, Scott J., committee member; Reddy, Anireddy S. N., committee member (Colorado State University. Libraries, 2018)
Palmer amaranth (Amaranthus palmeri) is a major weed in U.S. cotton and soybean production systems, partly because it evolved resistance to five different herbicide modes of action. Resistance to the 4-hydroxyphenylpyruvate dioxygenase (HPPD)-inhibitor tembotrione in a population from Nebraska (NER) is due to enhanced metabolism. This type of non-target-site resistance is especially troublesome because of its potential for cross-resistance. Tembotrione-susceptible (NES) and NER formed the same tembotrione metabolites but NER exhibited faster 4-hydroxylation followed by glycosylation. The T 50 value (time for 50% production of the maximum 4-hydroxylation product) was 4.9 and 11.9 h for NER and NES, respectively. Hydroxylation is typically catalyzed by cytochrome P450 monooxygenases (CYPs). Metabolism differences between NER and NES were most prominent under 28°C conditions and herbicide application at the four-leaf stage. An RNA-Seq transcriptome analysis was conducted with Pseudo-F 2 tembotrione-resistant and -susceptible individuals originating from three separate NER x NES crosses that were sampled before, six, and twelve h after treatment (HAT). Differential gene expression analysis identified CYP72A219 and CYP81E8 as strong candidates for metabolic resistance. The contigs were constitutively expressed in resistant plants, as were the contigs for several glycosyltransferases (GTs), oxidase, and glutathione-S-transferase (GST). Exposure to tembotrione further increased their expression in both resistant and susceptible plants. Originally native to the Southwest, A. palmeri has spread throughout the country. In 2004 a population was identified with resistance to glyphosate, a herbicide heavily relied on in modern no-tillage and transgenic glyphosate-resistant crop systems. Glyphosate resistance in the species is now highly prevalent in USA and was also discovered in Brazil in 2015. This was confirmed by species identification with a genetic marker, dose-response studies, shikimate accumulation assay, and EPSPS copy number assay. The Brazilian population was also resistant to sulfonylurea and imidazolinone ALS inhibitor herbicides conferred by two different alleles for target-site mutations in the ALS gene (W574L and S653N). The degree of genetic relatedness among eight different populations of glyphosate-resistant (GR) and –susceptible (GS) A. palmeri from various geographic regions in USA was investigated by analyzing patterns of phylogeography and diversity to ascertain whether resistance evolved independently or spread from outside to an Arizona locality (AZ-R). Shikimate accumulation and EPSPS genomic copy assays confirmed resistance or susceptibility. With a set of 1,351 single nucleotide polymorphisms (SNPs), discovered by genotyping-by-sequencing (GBS), UPGMA phylogenetic analysis, principal component analysis, Bayesian model-based clustering, and pairwise comparisons of genetic distances were conducted. A GR population from Tennessee and two GS populations from Georgia and Arizona were identified as genetically distinct while the remaining GS populations from Kansas, Arizona, and Nebraska clustered together with two GR populations from Arizona and Georgia. Within the latter group, AZ-R was most closely related to the GS populations from Kansas and Arizona followed by the GR population from Georgia. GR populations from Georgia and Tennessee were genetically distinct from each other. The data suggest the following two possible scenarios: either glyphosate resistance was introduced to the Arizona locality from the east, or resistance evolved independently in Arizona. Glyphosate resistance in the Georgia and Tennessee localities most likely evolved separately. Thus, modern farmers need to continue to diversify weed management practices and prevent seed dispersal to mitigate herbicide resistance evolution in A. palmeri.
Keywords: glyphosate resistance; HPPD inhibitor; herbicide resistance; metabolic resistance; Palmer amaranth; Amaranthus palmeri